A facile method to fabricate functionally integrated devices for oil/water separation1. Issue 10 (14th March 2015) - An, Qi; Zhang, Yihe; Lv, Kaikai; Luan, Xinglong; Zhang, Qian; Shi, Feng
<x xml:space="preserve">Abstract</x> In this paper, we present a facile method for the fabrication of a functionally integrated device, which has the multi-functions of the oil-containment boom, oil-sorption material, and water/oil-separating film, through a single immersion step in an ethanol solution of stearic acid.